PANDANGAN MAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM TERHADAP ETIKA DOSEN DALAM PELAYANAN AKADEMIK PADA FAKULTAS TARBIYAH DAN ILMU KEGURUAN IAIN PALANGKA RAYA - ABDULLAH ABDULLAH (Fitrah: Jurnal Kajian Ilmu-Ilmu Keislaman, 2017)
This research aims to know the positive and negative view of the students of Islamic Education Study Program (PAI) on the lecturers’ ethics in giving academic services at the Faculty of Education and Teacher Training of IAIN Palangka Raya, which include the lecturers’ ethics in giving the courses, guiding the Teaching Practice (Praktek Mengajar), and guiding students in doing their proposal and thesis. This research is based on the qualitative descriptive method. The subject is the PAI students of 2013 of the Faculty of Education and Teacher Training-IAIN Palangka Raya. Technically, the data are collected through interview and documentation. It is then analyzed through data reduction, data presentation, and conclusion. The techniques of examining the validity of data is with triangulation of the source and peer examination through discussion. The result of the research shows that: First, in developing the lecture: (1) Positive view tells about exemplary, polite attitude, friendly, discipline, giving advices, and having noble character, (2) Negative one about undisciplined attitude, and lack of awareness and of appreciation of ethical values; Second, in guiding the teaching practice: (1) Positive outlook includes friendly, good guiding, experienced, and competent. (2) Negative one says about lack of attention to the students in the guiding process during preparation or during the practice of teaching; Third, in guiding the proposal and thesis: (1) Positive outlook says about giving advices and suggestions, thorough in correcting student writing, serious in giving guidance and spending time efficiently (2) Negative outlook says about unfriendly when providing consultation, not keeping the appointment, not giving the confirmation if there is cancellation of appointment, and seeming not to care about the student’s need related to the proposal and thesis guidance.